2001
DOI: 10.1084/jem.194.5.645
|View full text |Cite
|
Sign up to set email alerts
|

Localized Gene-Specific Induction of Accessibility to V(D)j Recombination Induced by E2a and Early B Cell Factor in Nonlymphoid Cells

Abstract: Accessibility of immunoglobulin (Ig) gene segments to V(D)J recombination is highly regulated and is normally only achieved in B cell precursors. We previously showed that ectopic expression of E2A or early B cell factor (EBF) with recombination activating gene (RAG) induces rearrangement of IgH and IgL genes in nonlymphoid cells. VκI genes throughout the locus were induced to rearrange after transfection with E2A, suggesting that the entire Vκ locus was accessible. However, here we show that Ig loci are not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 45 publications
(70 reference statements)
4
72
0
Order By: Relevance
“…Indeed, we showed that E2A has the ability to bind directly to the conserved E-box site present downstream of Vk RSSs and to increase histone acetylation at these regions in BOSC23 cells, supporting the notion that the critical function of E2A to induce recombination might be to induce the local accessibility of rearranging gene segments by recruiting HAT complexes rather than to induce transcription itself. Furthermore, the observation that E2A directly binds to the promoter and RSS regions of the VkI gene family members may explain how E2A could induce localized genespecific accessibility, which was reported previously (43).…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, we showed that E2A has the ability to bind directly to the conserved E-box site present downstream of Vk RSSs and to increase histone acetylation at these regions in BOSC23 cells, supporting the notion that the critical function of E2A to induce recombination might be to induce the local accessibility of rearranging gene segments by recruiting HAT complexes rather than to induce transcription itself. Furthermore, the observation that E2A directly binds to the promoter and RSS regions of the VkI gene family members may explain how E2A could induce localized genespecific accessibility, which was reported previously (43).…”
Section: Discussionsupporting
confidence: 57%
“…Evidence for prolonged light-chain recombination in our series is also provided by the increased usage of more IGKJ-distal genes in IGKV-KDE versus IGKV-J rearrangements (especially in λ-CLL). This may be attributed to a shift in accessibility to the recombinase from the J-proximal to the J-distal parts of the IGK locus at more advanced stages in B-cell ontogeny (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of E2A in non-B cells was also found to induce germ-line Ig transcription and rearrangement, suggesting that E2A might play a key role in Ig gene regulation (19)(20)(21). More recent studies demonstrated that transfection of the kidney cell line BOSC23 with E2A and the RAG recombination machinery was sufficient to drive diverse recombination events at the Ig heavy and light chain loci (22,23). Overexpression studies have also implicated E2A in the regulation of other genes involved in the initiation and maintenance of the B cell developmental program.…”
mentioning
confidence: 99%